'Sharing my stories': genealogists and participatory heritage. Issue 3 (23rd February 2020) - Tasker, Gillian; Liew, Chern Li
ABSTRACT: The vision of an online participatory culture involving communities contributing information and engaging with digitized collections via the social Web has been challenged by the reality of low response rates to many digital cultural heritage projects. This study examines factors that encourage or discourage genealogists, a group generally motivated to share and exchange information, to contribute to DCH projects. The aim is to determine how they prefer to share information and knowledge and investigate if genealogists from indigenous communities have different preferences. Semi-structured interviews were conducted with six members of the New Zealand Society of Genealogists. The interview data were used to inform the design of an online survey questionnaire, which was distributed to other members of NZSG. The findings showed that respondents were willing to share information and were motivated to establish reciprocal relationships fundamental to building online communities. Lack of knowledge about cultural heritage databases and concerns over ownership, control and the reuse of information however, were identified as factors that discouraged sharing, especially for researchers of Māori genealogy. The survey findings suggest that cultural heritage institutions (CHIs) need to nurture relationships and earn the trust of the community from which information is being solicited. Effective consultation and communication and having clear policies in place about use and reuse of information shared could facilitate these. Further research into encouraging the exchange of information between CHIs and the indigenous communities is particularly important as many remain conflicted between their desire to share and to protect their family history and knowledge.